1998
DOI: 10.1002/prac.19983400110
|View full text |Cite
|
Sign up to set email alerts
|

1,3-Dithienium- und 1,3-Dithioleniumsalze. IX. Reaktionen von 1,3-Dithian-2-ylium-tetrafluoroboraten mitC-Nucleophilen

Abstract: 1,3‐Dithienium and 1,3‐Dithiolenium Salts. IX. Reactions of 1,3‐Dithiane‐2‐ylium Tetrafluoroborates with C‐Nucleophiles 1,3‐Dithian‐2‐ylium tetrafluoroborates (1), which can be easily obtained by variable methods, react in good to excellent yields with variable C‐nucleophiles to new geminal disubstituted 1,3‐dithianes. The latter compounds are potential precursors of interesting synthetic building blocks. Reactions are described with 2‐lithio‐1,3‐dithianes 2, sodium cyanide 4, sodium salts of the nitro alkanes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The solvent was filtered and evaporated. Flash chromatography (Hex:AcOEt, 95:5) yielded starting material 4a (20%, 39 mg, 0.20 mmol) and dimer 2 (27%, 53 mg, 0.14 mmol) as a white solid, with same spectral characterization as previously described …”
Section: Methodsmentioning
confidence: 89%
See 1 more Smart Citation
“…The solvent was filtered and evaporated. Flash chromatography (Hex:AcOEt, 95:5) yielded starting material 4a (20%, 39 mg, 0.20 mmol) and dimer 2 (27%, 53 mg, 0.14 mmol) as a white solid, with same spectral characterization as previously described …”
Section: Methodsmentioning
confidence: 89%
“…Flash chromatography (Hex:AcOEt, 95:5) yielded starting material 4a (20%, 39 mg, 0.20 mmol) and dimer 2 (27%, 53 mg, 0.14 mmol) as a white solid, with same spectral characterization as previously described. 49 2 : 1 H NMR (300 MHz, CDCl 3 ) δ ppm 7.54–7.15 (m, 10H), 2.70–2.49 (m, 8H), 2.01–1.75 (m, 4H). 13 C NMR (75 MHz, CDCl 3 ) δ ppm 135.0, 133.0, 127.6, 127.3, 70.9, 29.0, 24.7.…”
Section: Methodsmentioning
confidence: 99%
“…Our recent approach to the synthesis of α-arylazo-carbonyl compounds showed that easily available dithi(ol)anylium tetrafluoroborates [2728] (following shortened to TFBs) serve as stable precursors for ketene dithioacetals [29]. In accordance with previous work of others [30], they allow the addition of electrophiles in α-position independent of further presence of activating electron-withdrawing groups (EWGs). In the present study we will show the successful use of dithi(ol)anylium TFBs for the Michael-type addition to α,β-unsaturated ketones.…”
Section: Introductionmentioning
confidence: 87%